Novel histone deacetylase-5 inhibitor T2943 exerts an anti-depressive effect in mice by enhancing GRID1 expression - Juan Du; Ruyun Liu; Lin Ma; Yue Liu; Wei Wei; Ning Liu; Qiuhua Cao; Jianqiang Yu (Scientific Reports)
Abstract Histone deacetylase-5 (HDAC5) is implicated in the pathogenesis of depression and the mechanistic pathways underlying the effects of antidepressant medications. We previously identified a novel HDAC5 inhibitor, T2943, with antidepressant properties that promote histone 3 lysine-14 acetylation (H3K14ac) by inhibiting HDAC5 activity. In this study, we identify the core genes promoting transcription and expression following T2943-mediated upregulation of H3K14ac, highlighting Grid1 (GluD1) as a central gene. We used cleavage under targets and tagmentation (CUT&Tag), gene set enrichment analysis, and behavioral tests after GRID1 (glutamate receptor delta-1 subunit) knockdown. Gene ontology and pathway enrichment analysis via CUT&Tag suggested the following mechanism for the antidepressant action of T2943: T2943 inhibits HDAC5 activity to promote H3K14 acetylation. This modification loosens the chromatin structure, allowing transcription factors to bind to the Grid1 promoter region and enhance its transcription and expression. Upregulated GRID1 mediates signal transmission in neural pathways, restores the regenerative ability of hippocampal nerve cells, promotes nerve growth and synaptic formation, increases synapse numbers, and enhances synaptic function. Our findings highlight the therapeutic potential of targeting HDAC5 in depression and clarify the antidepressant mechanism of T2943.